Mempelajari Karakteristik Pengeringan Lapis Tipis Jeroan Ayam - Sitepu, Mia Anjelina; Tamrin, Tamrin; Rahmawati, Winda; Kuncoro, Sapto (abe.fp.unila.ac.id, 2022)
The poultry industry in Indonesia is growing rapidly, but still relies heavily on the supply of seeds and feed raw materials from abroad. The abundant meat production leaves innards or chicken carcasses in large quantities. The use of chicken innards into animal feed is one of the fulfillments of the supply of animal feed availability because it contains enough protein. Because the period of decomposition of meat occurs quickly, so to overcome this, it is necessary to dry the dried innards in order to stay durable. This study aims to determine the characteristic value and water content of the equilibrium drying of chicken innards thin-layer as well as observe the color changes of chicken innards. The study was conducted by an experimental method with two treatments, namely drying temperature and innards type. The analyses carried out are water content, equilibrium water content (Me), drying constant (k), protein, and color. From the results of the study, it was found that the type of innards (gizzard, liver, and intestine) affects the drying time, final water content, protein, and color but does not affect the equilibrium water content (Me), and the drying constant. While the drying temperature used affects all observed parameters. High temperatures (90°C) produce brighter colors because the drying process is shorter. Keywords: Chicken innards, Color, Layer Drying, Thin Protein.